REVITALIZATION OF THE MANGROVE AREA ON THE COASTAL COAST OF LOBUK VILLAGE - Ferdiansyah, Akhmad; Mutiati, Enni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Coastal areas that have an essential role in developing the environmental sector and improving air quality in Sumenep Regency are coastlines with mangroves as the primary vegetation in the coastal ecosystem. There are currently many problems directly related to coastal conditions in mangrove forests. Several villages in the district have mangrove vegetation that is not maintained, and in certain parts, it can even be said that the mangrove vegetation in these areas is seriously damaged. This can be seen from the absence of vegetation/mangrove species that grow well, including the coast in Lobuk Village and Bluto District. So, efforts to preserve mangrove forests are significant to carry out. Community service activities with the theme of revitalizing the mangrove area on the coast of Lobuk Village, Bluto District, aim to restore the primary function of the mangrove forest along the coast of Lobuk Village by maintaining mangrove plants as an effort to improve the ecosystem and mangrove vegetation and reduce the impact of coastal erosion. The activities include site inspection, outreach, training, planting and monitoring of planting results. The results obtained in the mangrove area revitalization activities on the coast of Lobuk Village, Bluto District, based on the third monitoring activity, recorded that 50.67% of the success of mangrove growth was in the pretty good growth category, increase in the Rhizhopora stylosa species was 51.66% in the fairly good growth category, species Ceriops decandra was 48% in the pretty good growth category, the Bruguera gymnorrhiza species was 40% in the reasonably good growth category and growth in the Sonneratia alba species was 63% in the excellent growth category.